A Protein with Unknown Function, Ps495620, Is Critical for the Sporulation and Oospore Production of Phytophthora sojae - Xiaoran Du; Yan Zeng; Yiying Li; Qin Peng; Jianqiang Miao; Xili Liu (Journal of Fungi)
While the rapid rise in bioinformatics has facilitated the identification of the domains and functions of many proteins, some still have no domain annotation or largely uncharacterized functions. However, the biological roles of unknown proteins were not clear in oomycetes. An analysis of the Phytophthora sojae genome database identified the protein Ps495620, which has no domain annotations and functional predictions in Phytophthora. This study used a CRISPR/Cas9-mediated gene replacement system to knock out Ps495620 to elucidate its function. The Ps495620-knockout mutants exhibited significantly increased oospore production and decreased sporangium formation compared to the wild-type strain P6497. Transcriptomics showed that it is a key regulator of nitrogen, pyruvate, ascorbate, and adorate metabolism in P. sojae. Our findings indicate that Ps495620 is critical in regulating sporangium formation and oospore production in P. sojae.